Assessment of three-dimensional effects on slamming load predictions using OpenFoam. (July 2021) - Wang, Shan; Xiang, Gong; Guedes Soares, C.
Abstract: Three-dimensional effects on slamming loads predictions are investigated numerically using the unsteady incompressible Reynolds-Average Navier-Stokes (RANS) equations and volume of fluid (VOF) method, which are implemented in the open-source library OpenFoam. Three cases of free-falling water entry problems are considered. The numerical solutions are validated through the comparisons of slamming loads and motions between the CFD simulations and the available experimental values. The total slamming force and slamming pressures on the 3D wedge cylinder, ship section and slender circular cylinder are compared with the results on the 2D sections, respectively. The results show that the 3D predictions on the maximum slamming force coefficient are around 21%∼23% lower for the wedge with a deadrise angle of 30º and are around 16% lower for the slender circular cylinder, relative to the 2D calculations.